Geoportale del Consorzio LaMMA Disseminazione di dati meteo in near real-time tramite standard OGC e software Open Source - Giannechini, Simone; Mari, Riccardo; Corongiu, Manuela; Bottai, Lorenzo; Fibbi, Luca; Pasi, Francesco (GEOmedia, 2014)
This paper describes the spatial data infrastructure (SDI) used by the LaMMA Consortium - Environmental Mod elling and Monitoring Laboratory for Sustainable Developm ent of Tuscany Region for sharing, viewing and cataloguing (metadata and related information) all geospatial data that are daily proc essed and used op erationally in many meteorological and environmental app lications. The SDI was develop ed using Open Source technologies, mo reover the geospatial data has been imp lemented through protoco ls based on ogc (Open Geospatial Consortium) standards such as WMS, WFS and CSW. Geoserver was used for disseminating geospatial data and maps through OGC WMS and WFS protoco ls while GeoNetwork was used as the cataloguing and search po rtal through also the CSW protocol; eventually MapStore was used to implement the mash-up front-end. The innovative aspect of this po rtal is the fact that it currently is ingesting, fusing and disseminating geospatial data related to the MetOcfield from various sources in near real-time in a comp rehensive manner that allows users to create add ed value visualizations for the support of operational use cases as well as to access and download underlying data (where app licable).